Goldilocks and the Three Bears = - Lomba, Ana (McGraw-Hill, 2006)
Award-winning language-learning innovator Ana Lomba transforms “Goldilocks and the Three Bears” into a way to introduce kids ages two to seven to French. It includes vivid illustrations, a mini “pictionary,” and frequent dialogs that model everyday communication. Accompanying the book is a 45-minute audio CD that features a lively reading of the story, in French and English, helpful pronunciation basics, and fun games and activities.